Assessment of groundwater leakage source using hydrochemical data and isotopes in the Pandanduri dam tunnel, Lombok Island, Indonesia - Heru Hendrayana; Doni Prakasa Eka Putra; Hendy Setiawan; I Gde Budi Indrawan; Wawan Budianta; Wahyu Wilopo (Brawijaya University, 2022)
Leakage or seepage in reservoirs and dams has the potential for structural instabilities persuaded by water leakage pathways and linked to economic consequences. An environmental isotopic and hydrochemical research was conducted to determine the source and origin of seepages on the tunnel of Pandanduri dam, Lombok Island, Indonesia. This study aimed to examine the source of the tunnel leak on the dam site and the origin or source of water at the point of leakage based on water chemistry data and stable isotopes. To identify the source of the leakage water in the tunnel dam, 33 samples of the leakage water, groundwater, reservoir water, river water, and rainfall water were taken for chemical and isotopic composition analysis. The field measured the reservoir level, spring discharges, and physicochemical parameters (EC, pH, TDS, TSS). The physicochemical parameters show that the leakages water is similar to reservoir water. The types of leakage water in the tunnel belong to alkaline water, predominantly sulfate-chloride. This type of water is deep groundwater with a higher sulfate and chloride concentration than surface water or shallow groundwater. Hydrochemical and isotope analysis showed that water origin at leakage points is dominated by groundwater.